Manajemen Madrasah Ramah Anak Berbasis Pesantren: Studi Multisitus pada MA Asy-Syifa dan MA Raadhiyatan Mardhiyyah Putra Balikpapan - Muhamad Abdulloh Afandi; Muhammad Tahir; Agus Setiawan (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2026)
Violence against children in educational settings, including Islamic boarding school-based institutions, remains a significant challenge, highlighting the need for child protection programs that are effectively integrated into institutional management. This study aims to examine the management of the Child-Friendly Madrasah (Madrasah Ramah Anak/MRA) program in Islamic boarding school-based madrasahs and to develop a conceptual model derived from a multi-site analysis. A qualitative multi-site design was employed at MA Asy-Syifa Balikpapan and MA Raadhiyatan Mardhiyyah Putra Balikpapan. Data were collected through in-depth interviews, observations, and document analysis involving principals, vice principals, teachers, dormitory supervisors, and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña through within-site and cross-site analysis. The findings reveal that the Child-Friendly Madrasah program is implemented through the integrated application of the four core management functions: planning, organizing, actuating, and controlling, all of which are aligned with the values of the Islamic boarding school tradition. Successful implementation is supported by strong leadership commitment, collaboration among stakeholders, a positive pesantren culture, and parental involvement. However, several challenges remain, including hierarchical organizational culture, resistance to change, limited understanding of child-friendly education principles, and the complexity of managing students in a twenty-four-hour boarding environment. The study proposes a Pesantren-Based Child-Friendly Madrasah Management Model, demonstrating that effective implementation depends not only on compliance with child protection policies but also on the integration of educational management functions with Islamic boarding school values to create a safe, religious, disciplined, participatory, and child-centered learning environment.